2015
DOI: 10.4236/msce.2015.38006
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Modelling of Oil from <i>Eucalyptus camadulensis by</i> Organic Solvent

Abstract: This work was conducted to study the extraction of eucalyptus oil from natural plants (Eucalyptus camadulensis leaves) by organic solvents. the effects of the main operating parameters were studied; type of solvent (n-hexane and ethanol), time to reach equilibrium, the temperature (45˚C to 65˚C) for n-hexane and (45˚C to 75˚C) for ethanol, solvent to solid ratio (5:1 to 8:1 (v/w)), agitation speed (0 to 900 rpm) and the particle size (0.5 to 2.5 cm) of fresh leaves to find the best processing conditions for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The interaction of these two independent variables is also of importance. This condition is consistent with the report by Abed et al (2015). They reported that the speed of stirrer improved mass transfer and eddy diffusion in the solvent at the particle surfaces.…”
Section: Contour Plotssupporting
confidence: 93%
See 1 more Smart Citation
“…The interaction of these two independent variables is also of importance. This condition is consistent with the report by Abed et al (2015). They reported that the speed of stirrer improved mass transfer and eddy diffusion in the solvent at the particle surfaces.…”
Section: Contour Plotssupporting
confidence: 93%
“…They reported that the speed of stirrer improved mass transfer and eddy diffusion in the solvent at the particle surfaces. Moreover, increasing the ratio of solvent-to-solid will increase the oil yield, up to some limit, because the concentration gradient in liquid phase increases as dissolved substances are diluted, and this favors good mass transfer (Abed et al, 2015). Fig.…”
Section: Contour Plotsmentioning
confidence: 99%
“…When t approaches 0 the initial extraction rate, hi, as , can be written as equation (6): (6) At any time, the concentration of peppermint oil can be expressed as:…”
Section: Kinetic Model Of Peppermint Oil Extractionmentioning
confidence: 99%
“…Essential oils are generally colorless to slightly yellowish and only slightly soluble in water and dissolve fairly well in an organic solvent and mix very well with vegetable oils and fats. Many essential oils have antibacterial, anti-fungal, and antiparasitic properties [5], [6].…”
Section: -Introductionmentioning
confidence: 99%
“…Examples of these solvent are benzene, hexane, acetone, petroleum ether, ethyl alcohol, etc. [3][4][5][6][7]. The industrial application of solvent extraction method is increasing day by day because of their direct application to a wide range of raw materials with low oil content [8][9][10].…”
Section: Introductionmentioning
confidence: 99%